Development of a Pan-Filoviridae SYBR Green qPCR Assay for Biosurveillance Studies in Bats - Coertse, Jessica; Mortlock, Marinda; Grobbelaar, Antoinette; Moolla, Naazneen; Markotter, Wanda; Weyer, Jacqueline (Viruses, 2023)
Recent studies have indicated that bats are hosts to diverse filoviruses. Currently, no pan-filovirus molecular assays are available that have been evaluated for the detection of all mammalian filoviruses. In this study, a two-step pan-filovirus SYBR Green real-time PCR assay targeting the nucleoprotein gene was developed for filovirus surveillance in bats. Synthetic constructs were designed as representatives of nine filovirus species and used to evaluate the assay. This assay detected all synthetic constructs included with an analytical sensitivity of 3–31.7 copies/reaction and was evaluated against the field collected samples. The assay’s performance was similar to a previously published probe based assay for detecting Ebola- and Marburgvirus. The developed pan-filovirus SYBR Green assay will allow for more affordable and sensitive detection of mammalian filoviruses in bat samples.